International Tax Co-operation and Capital Mobility. - FitzGerald, V (Routledge, 2002)
The international mobility of capital and the geographical dispersion of firms have clear advantages for the growth and modernization of developing countries. They also create fundamental challenges for national tax authorities. Modern principles of capital taxation for the open developing economy indicate the need to find the correct balance between the encouragement of private investment and the finance of social infrastructure, both of which are necessary for sustainable growth. This balance can be sub-optimal where countries compete for inward investment by granting tax incentives or exercise conflicting principles in determining the tax base. The current practice of international taxation indicates that fiscal authorities in Latin America and the Caribbean could attain a more equitable share of capital tax revenue without depressing investment and growth. This might be achieved through more effective regional tax rules, double taxation treaties, information sharing and treatment of offshore financial centres along the lines already promoted for OECD members. These findings have wider implications for developing countries as a whole.